2017
DOI: 10.1111/ajt.14283
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Receptor Genes Associated With Tolerance Identify a Cohort of Immunosuppressed Patients With Improved Renal Allograft Graft Function

Abstract: We previously reported that two B cell receptor genes, IGKV1D-13 and IGKV4-1, were associated with tolerance following kidney transplantation. To assess the potential utility of this “signature” we conducted a prospective, multicenter study to determine the frequency of patients predicted tolerant within a cohort of patients deemed to be candidates for immunosuppressive minimization. At any single time point 25 – 30% of patients were predicted to be tolerant, while 13.7% consistently displayed the tolerance “s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…More recent evidence in the operationally tolerant human kidney transplant recipients has identified the same B‐cell signature of tolerance by transcriptional analysis of peripheral blood in both spontaneously tolerant individuals as well as those who underwent specific tolerance induction protocols . In addition, a significant proportion of patients with stable long‐term graft function while on immunosuppression demonstrated this B‐cell tolerance signature . A recent meta‐analysis of the gene signatures of operationally tolerant kidney transplant patients validated the concept that the majority of biomarkers associated with tolerance were in fact B‐cell‐related .…”
Section: B‐cell Signature Of Transplant Tolerancementioning
confidence: 89%
“…More recent evidence in the operationally tolerant human kidney transplant recipients has identified the same B‐cell signature of tolerance by transcriptional analysis of peripheral blood in both spontaneously tolerant individuals as well as those who underwent specific tolerance induction protocols . In addition, a significant proportion of patients with stable long‐term graft function while on immunosuppression demonstrated this B‐cell tolerance signature . A recent meta‐analysis of the gene signatures of operationally tolerant kidney transplant patients validated the concept that the majority of biomarkers associated with tolerance were in fact B‐cell‐related .…”
Section: B‐cell Signature Of Transplant Tolerancementioning
confidence: 89%
“…Moreover, it was impossible to compare the prescription patterns of immunosuppressive drugs in patients with LTGS, which might affect the gene expression related to immune cells. A recently published study demonstrated that the expression levels of IGKV1D-13 and IGKV4-1 were increased by tacrolimus and decreased by steroids, mycophenolate mofetil, or thymoglobulin treatment ( 31 ), suggesting the importance of the effects of drugs in the interpretation of transcriptomic data. We could not exclude the possibility that the molecular and phenotypic features of patients with OT simply originated from the lack of immunosuppressive agents, rather than specific immunological characteristics of tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Tolerance (GAMBIT) study in Europe. 133 Nevertheless, some authors still support the notion that the expression of B-cell receptor genes, IGKV1D-13 and IGKV4-1, is a clinically relevant biomarker in kidney transplantation, 134 whereas others consider that the effect of immunosuppressive drugs is still misleading the results. 129 Their results showed that the percentage of transitional B cells increased significantly after steroid withdrawal, suggesting that the increment of regulatory B cells in tolerant patients could be a consequence of steroid withdrawal rather than a true biomarker of tolerance.…”
Section: Other Mechanisms Of Breg Functionmentioning
confidence: 99%
“…129 Interestingly, another independent study that evaluated tolerance biomarkers (in particular the expression of IGKV1D-13 and IGKV4-1 genes obtained from Newell et al 125 Having shown that immunosuppressive drugs drastically affect circulating B-cell proportions, it is difficult to conclude with certainty that gene signatures in B cells can be used to indicate operational tolerance in renal transplant recipients. 133 Nevertheless, some authors still support the notion that the expression of B-cell receptor genes, IGKV1D-13 and IGKV4-1, is a clinically relevant biomarker in kidney transplantation, 134 whereas others consider that the effect of immunosuppressive drugs is still misleading the results. 135,136 This interesting debate has allowed the definitions of biomarkers of tolerance to be refined.…”
Section: Other Mechanisms Of Breg Functionmentioning
confidence: 99%